Dynamics of interaction of lactic acid microorganisms in paired consortia aiming at fermentation of vegetable raw materials - V. V. Kondratenko; N. E. Posokina; J. A. Semenova (Овощи России)
Relevance. Cabbage is one of the most popular products, which is mainly fermented with the addition of various vegetables. When fermentation is not only the original nutrients such as vitamin C, amino acids, dietary fibers, etc., but also develop functional microorganisms such as lactic acid bacteria. Fermentation has an important effect on the quality and taste of cabbage, so it is important to study the fermentation process, microbial diversity and changes in nutrients and chemical elements in the fermentation process. L. mesenteroides is considered to be the dominant species on heterofermentative early stages of fermentation. However, there is little information on the diversity of species and strains of Leuconostoc involved in fermentation of sauerkraut. Studies that used traditional biochemical methods to study fermentation of sauerkraut showed that four main types of lactic acid bacteria were involved in the fermentation process: Leuconostoc mesenteroides, Lactobacillus plantarum, Pediococcus pentosaceus and Lactobacillus brevis. Taking into account the importance of two-stage fermentation of vegetable raw materials in order to create optimal conditions for the development of the "main" pool of lactic acid microorganisms at the first stage, it becomes urgent to conduct a complex of studies aimed at reproducing the "natural" process in which the main role is played by bacteria of the genus Leuconostoc mesenteroides at the second stage – monocultures of lactic acid microorganisms and their consortia.Methods. The paper studies the dynamics of the type of interaction of lactic acid microorganisms in paired consortiums on model media pretreated by the culture of the species Leuconostoc mesenteroides, at the main stage of step fermentation of white cabbage of the "Parus" variety.Results. It is established that the sum of the criteria, the consortium "L. mesenteroides \ L. casei + L. plantarum" demonstrates the most pronounced advantage compared with monoculture cultivation of appropriate format of pseudotensorial; despite the pronounced synergy in the cultivation of the consortium "L. mesenteroides \ L. brevis + L. plantarum", the dynamics of the comparison index on the rate of increase in the concentration of microorganisms indicates the need for additional research.